The Challenge of Ecophysiological Biodiversity for Biotechnological Applications of Marine Microalgae - Lucia Barra; Raghu Chandrasekaran; Federico Corato; Christophe Brunet (Marine Drugs, 2014)
In this review, we aim to explore the potential of microalgal biodiversity and ecology for biotechnological use. A deeper exploration of the biodiversity richness and ecophysiological properties of microalgae is crucial for enhancing their use for applicative purposes. After describing the actual biotechnological use of microalgae, we consider the multiple faces of taxonomical, morphological, functional and ecophysiological biodiversity of these organisms, and investigate how these properties could better serve the biotechnological field. Lastly, we propose new approaches to enhancing microalgal growth, photosynthesis, and synthesis of valuable products used in biotechnological fields, mainly focusing on culture conditions, especially light manipulations and genetic modifications.